Research on the structure and performance of carbon fiber composite carbody for high-speed maglev transportation - WANG Jianbo; SHAO Qing; LIU Haiping; REN Zhonghua; LI Gang; YU Qingsong (机车电传动)
Maglev transportation represents a high-speed, safe, energy-efficient, environmentally-friendly, and sustainable mode of travel, with great development potential. However, the aerodynamic loads generated by maglev trains operating at speeds exceeding 600 km/h impose stringent requirements on carbody strength, creating an urgent need for relevant studies. This paper analyzed the composite carbody structure of high-speed maglev trains, and researched a novel carbody structure composed of carbon fiber composite plates and aluminum alloy profiles. Based on ANSYS, a numerical calculation model was constructed to analyze the main performance characteristics of carbodies, such as stiffness, strength and modals. These analyses confirmed compliance with the load requirements for train operation faster than 600 km/h. The simulation results indicate a maximum deflection of 1 mm at the lower chord beam under vertical load conditions and a natural vibration frequency of 7.88 Hz in the first-order vertical bending mode for carbodies under the servicing state, in alignment with the stiffness and modal requirements throughout the whole lifecycle of carbodies. Furthermore, based on the modified Brown-Miller equation for strain life, the fatigue life of the carbody structure was analyzed by applying the Fe-safe software and Tsai-Wu failure criterion. The calculations reveal that the maximum stress in the composite sandwich plates occurs at the underframe composite sandwich board under condition 3, which meets the design requirements for fatigue strength. Compared with the maglev trains put into commercial operation on the Shanghai demonstration line, the proposed carbody structure achieves a mass reduction by 6.7%. The study findings provide a theoretical basis and engineering experience for future speed increase and lightweight design of maglev trains.